2000
DOI: 10.1017/s0032247400016247
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the veil: the circumstances that caused Alfred Wegener's death on the Greenland icecap, 1930

Abstract: When the Geographical Society of Berlin officially welcomed Alfred Wegener's expedition back from Greenland in 1931, a memorial address was made in honour of the expedition leader who died on the Greenland icecap in 1930. This address included a report that shed light on the difficulties that had confronted the expediton. Wegener was remembered as a researcher who provided an example of ‘a magnificent conception of his duty as leader’ and who risked his life to rescue his comrades. Wegener's death was blamed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This paper is part of the continuing stream of managerial studies of polar exploration found in the work of both management and polar scholars. These include Barr's study of organisational disintegration, Stuster's comprehensive study of behavioural issues in polar and space exploration, Lüdecke's evaluation of Alfred Wegener's fateful expedition in Greenland, studies by Perkins and others, Morrell and Capparell, and Useem on the question of leadership especially that of Ernest Shackleton, Karpoff's analysis of private versus public expeditions, and Savitt's examination of explicit and tacit knowledge in sledging (Barr 1984;Stuster 1996;Lüdecke 2000;Perkins and others 2000;Morrell and Capparell 2001;Useem 1988;Karpoff 2001;Savitt 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is part of the continuing stream of managerial studies of polar exploration found in the work of both management and polar scholars. These include Barr's study of organisational disintegration, Stuster's comprehensive study of behavioural issues in polar and space exploration, Lüdecke's evaluation of Alfred Wegener's fateful expedition in Greenland, studies by Perkins and others, Morrell and Capparell, and Useem on the question of leadership especially that of Ernest Shackleton, Karpoff's analysis of private versus public expeditions, and Savitt's examination of explicit and tacit knowledge in sledging (Barr 1984;Stuster 1996;Lüdecke 2000;Perkins and others 2000;Morrell and Capparell 2001;Useem 1988;Karpoff 2001;Savitt 2004).…”
Section: Methodsmentioning
confidence: 99%
“…He died on 13 March 1938 in London. He is remembered today primarily for his unexpected meeting in 1896 with Fridtjof Nansen (1861-1930, his new exploration practices, especially the use of ponies for transport that influenced British Antarctic expeditions, and his focus on science as an exploration goal (Mills 2003 I: 328). Jackson also made contributions to geography, science and management practice.…”
Section: Introductionmentioning
confidence: 99%
“…Chief among them, he indicates, were an over-reliance upon the motor sledges, which failed; a lack of effort to communicate via radios, although they had been brought out with the expedition supplies; miscommunications between Wegener and various expedition members; and unexpectedly harsh weather and ice conditions. However, disappointingly, the book does not delve into a number of other issues raised in an important article in this journal by Cornelia Lüdecke (2000). In fact, that article and many of the primary documents and other sources referenced in it are never cited or acknowledged in this book.…”
mentioning
confidence: 99%
“…Wegener had hoped to use aircraft to establish Eismitte, but the idea was quashed by the funding body due to its cost. Later, when a search for Wegener was organised, the Notgemeinschaft vetoed the use of aircraft — including those of Gino Watkins, which were already being used on the Greenland icecap — on the grounds that ‘the reputation and success of the expedition [would] be endangered.’ The Notgemeinschaft determined that if no aircraft were used in the search, the public would assume it was impossible to use them and would not blame the organisation (Lüdecke 2000: 146).…”
mentioning
confidence: 99%
See 1 more Smart Citation